Consumer Reviews, Ratings, and Gamification on Muslim Millennials’ Online Purchasing Decisions - Septi Kurnia Prastiwi; Asep Maulana Rohimat; Helti Nur Aisyiah (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Since previous research on the relationship among Online Consumer Review (OCR), ratings, gamification, and online purchasing decisions had mixed results, this study involves trust as a mediating variable, which has never been explored in previous research, to explore online consumer reviews, ratings, and gamification in increasing trust of Muslim Millennials for online purchasing decisions. Investigating Muslim millennials in Central Java and Yogyakarta, 114 questionnaire results were analyzed using Structural Equation Model. The results showed that OCR and ratings affect Muslim Millennials' online purchasing decisions at Shopee, while gamification cannot affect them. Trust in this research model could not affect purchasing decisions. Thus, the trust could not be a mediating variable. The results of this study will be useful for Micro, Small and Medium Enterprises (MSMEs) and the online shop’s development team to maintain the image of an online store.